Leukocyte Glucose Index as Significant Marker of Poor Prognosis in COVID-19 Patients with Hyperglycemia (Bangladesh Journal of Infectious Diseases, 2025)
Background: Both diabetes mellitus (DM) and stress hyperglycemia (SH) are common findings in complicated or critically ill COVID-19 patients.Objective: This retrospective study aims to assess leukocyte glucose index (LGI) as a prognostic marker for the outcome of COVID-19 patients.Methodology: This retrospective study was conducted at the College of Medicine, University of Diyala, Iraq. Patients with COVID-19 were randomly allocated. A primary outcome of this study was clinical outcomes in terms of surviving or not surviving.Results: 187 patients in total were included in the study and divided into three groups. Group I (n = 45) survived patients, Group II (n = 90) survived patients with complications, and Group III (n = 52) non-survived patients. The baseline data showed significant differences between Groups III, I, and II. The median values of LGI were significantly (p